The Lease of the Philadelphia Gas-Works - Lewis, William Draper (Quarterly Journal of Economics, 1898)
Journal Article The Lease of the Philadelphia Gas-Works Get access William Draper Lewis William Draper Lewis Philadelphia Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 12, Issue 2, January 1898, Pages 209–224, https://doi.org/10.2307/1882119 Published: 01 January 1898